Controle da mancha angular e análise bioquímica de resistência em feijoeiro tratado com extratos de Pycnoporus sanguineus - Viecelli, Clair Aparecida (2008)
The alternative control of plants disease aims to minimize ambient impacts by the use of natural products. With the possibility of using Pycnoporus sanguineus extracts for the control of pathogenic fungus, this work was conduced to verify the antimicrobial activity in vitro against Pseudocercospora griseola and the induction of enzyme defense in bean plant as peroxidase, polyphenol oxidase and β-1,3-glucanase and activation of physiological mechanisms related to the energy supply, as proteins and chlorophyll. The experiments in vitro and in greenhouse had been constituted by extracts from basidiocarps, mycelium and liquid medium culture filtrate of P. sanguineus. Water, acibenzolar-S-methyl (ASM: 75 mg i.a. L-1) and fungicide (azoxystrobin: 40 mg i.a. L-1) were the control treatments. In vitro, the extract of mycelium at 5%, sterilized by filtration, significantly inhibited the mycelial growth, sporulation and conidia germination of P. griseola, what did not occur in the extract sterilized in autoclave, indicating the presence of thermo-sensible compounds. In greenhouse, bean plants had been treated three days before the inoculation with the pathogen and were evaluated the severity and the activity of plant defense enzymes peroxidase, β-1,3-glucanase and polyphenol oxidase in 3rd leaves treated as well as in 4th leaves not treated, to verify the occurrence of local or systemic resistance induction, respectively. Severity was reduced in 82.4% and 77% in 3rd leaves and in 71.6% and 69.4% in 4th leaves to P. sanguineus extracts at concentrations of 10% and 20%, respectively. In the field, severity was reduced in 19.2% and 63.8% in 1st and 2nd application, respectively, in relation to the control water. The activities of peroxidase, polyphenol oxidase, proteins and chlorophylls had an increment in plants treated with extracts. These results indicate the potential of P. sanguineus for alternative control of the angular leaf spot in bean plants